ANALISA VARIASI JUMLAH LILITAN PADA ALAT PENGHEMAT BAHAN BAKAR TERHADAP EMISI GAS BUANG MOTOR BENSIN 4 LANGKAH - Pratama PEP; Digdo Listyadi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2014)
Process combustion of fuel in room burn to be influenced by many factor , among others is temperature, closeness of mixture, composition, and turbulensi exist in mixture. When fuel temperature with air mount, hence will progressively easy to fuel with the air to on fire.Gas emission throw away which is yielded from combustion process at motor vehicle can have the character of poison and make negative effect at environment around, the mentioned in causing by less perfect combustion process, gas result of less the combustion perfect for example is CO, HC.The purpose of this study was to determine the effect of the use of electromagnets in the fuel line gasolin engine 4 step with variations in the number of windings on exhaust emissions and fuel consumption . The study was conducted in Laboratory Convert Energi Majors Technical Engineering Faculty Of Technique University Jember . Equipments which is used in the testing is Motor gasoline 4 Step with machine brand Honda Supra x 125D, Gas Analyzer , buret, measure glass, stop wach, tachometer , and accumulator 12 volt. used by materials is Premium RON 88, strand of metal have diameter to 0,6 cm, pipe have diameter to 1